DNA Contents in Soil Contaminated with Heavy Metals - Agnieszka Wolińska; Artur Marek Banach; Agnieszka Kuźniar; Zofia Stępniewska; Marta Kłos (The Global Environmental Engineers, 2014)
The study was performed to show how industrial activity affected soil quality in terms of soil DNA quality and quantity as well as soil characteristics. Soil material originated from an urban area of the Silesia Region (SW Poland). The soil characteristics were estimated: texture, moisture, pH, redox potential (Eh), and total carbon content (TOC), followed by determination of selected heavy metals (Pb, Cd, Zn, Cr, Fe, Cu). The last step was the isolation of soil DNA, its concentration and identification of microorganisms. The results showed that although the studied soil was heavily contaminated with heavy metals, there were still some metal-resistant microorganisms able to sustain soil activity. Moreover, these organisms are not present in the NCBI database, which encourages further studies aimed at identification of new organisms that may be useful in research of metal resistance as well as soil reclamation and remediation.